Effects of biotic resistance and resource availability on the invasion success of the Argentine ant, Linepithema humile (Mayr), in the Cape Floristic Region, South Africa - Mothapo, Natasha Palesa (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.